Capacity development for the transformation of Africa - Frannie A. Léautier (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Countries need capacity for a variety of reasons, including sustaining economic growth, generating jobs, reducing poverty, effectively managing development programmes, and transforming societies and economies. A lot of effort has been expended to develop capacity in Africa with mixed results. This paper provides a working definition of capacity that is relevant for a variety of African contexts, including stages of development achieved, the unique characteristics and challenges facing the continent, and the starting levels of endowment. The paper includes concepts of capability, staying power, human capital, and organizational performance, as well as introduces interpretations from co-evolutionary dynamics and the role of 'animal spirits' in capacity development policies. The special case of capacity development in crisis is included. Practical examples from practice are introduced and original empirical analysis provided to illustrate key concepts.
Keywords: A1; F00; O1; Q00; 330; Africa; animal spirits; capacity economic transformation; human capital; institutions; performance; policy